Pompeius Trogus and the Romanization of History (Note to Iust. 41.2.1-2) - Borgna, Alice (Anabasis. Studia Classica et Orientalia, 2019)
The paper intends to show how Justin’s Epitoma, despite being a work much easier to read in pieces than as a continuous whole, from a philological point of view must be considered as a unit, to avoid the risk of underestimating its most significant and pervasive aspects. Among these stands out the color Romanus, i.e. the application of Roman terminology to foreign countries, an essential means by which Trogus tries to bring closer to its readership the history of civilizations distant in time and space. Thanks to an analysis focused on the color Romanus in greater detail and on a full scale, it is possible to give a new interpretation of one of the much-debated passages of the Epitoma, Iust. 41.2.1–2, and call into question the famous conjecture probulorum proposed by Alfred von Gutschmid.